Demographic Profile and Neuro-Ophthalmic Manifestations in Primary Intracranial Tumours in Adult Patients: An Observational Study from a Tertiary Care Health Centre in Eastern India - Suchismita Mishra; Souvagya Panigrahi; Suprava Das; Yamijala Neha Srija; Pradeep Kumar Panigrahi; Manaswini Patro (TNOA Journal of Ophthalmic Science and Research)
Purpose: To evaluate the demographic profile and neuro-ophthalmic manifestations of primary brain tumours in adult patients presenting to a tertiary care centre in eastern India. Methods: A hospital-based cross-sectional study was conducted on patients with primary intracranial tumours presenting to a tertiary care multi-specialty hospital in eastern India from January 2018 to October 2021. A complete neurosurgical, endocrinal, and ophthalmological evaluation was done in each patient. Results: A total of 106 patients with primary brain tumours were included in the study. The mean age of presentation was 40.98 ± 12.85 years. There were 50 (47.17%) males and 56 (52.83%) females. The tumour location was supratentorial (ST) in 72 (67.92%) patients and infratentorial (IT) in 34 (32.08%) patients. Pituitary adenoma was the most common tumour in the present study (32.07%). The most common tumour was pituitary adenoma in the ST location and cerebellopontine angle schwannoma in the IT location. Headache and hearing loss were the most common presenting symptoms in ST and IT tumours, respectively. Blurring of vision was the most common ocular symptom in 47.16% of cases. Hemianopic field defect was the most common field defect in our study and was seen in 47.72% of cases. Conclusion: Meticulous ophthalmological examination is essential in patients with intracranial tumours. Our study emphasises the importance of a detailed ophthalmological examination and knowledge of associated neurological manifestations in ST and IT tumours.